Comparative Analysis of Deciduous Teeth Eruption and Carpal Bone Ossification for Forensic age Estimation in Children Aged 5–15 Years - Shahida Naveed, Amber, Faqir Ullah, Ghulam Muhayudin, Wazir Ahmed, Ijaz Aziz (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate and compare the accuracy of deciduous teeth eruption (using the Demirjian method) and carpal bone ossification (using the Greulich and Pyle method) for forensic age estimation in children aged 5 to 15 years. Methods: This randomized controlled trial included 146 children of both genders, aged 5–15 years, who were divided into two groups: Group A (dental age estimation) and Group B (skeletal age estimation). Group A utilized dental radiographs of the left mandibular quadrant, and Group B utilized radiographs of the right wrist for skeletal age estimation. The statistical differences between chronological age and estimated age for both methods were calculated using SPSS version 24. Results: The sample consisted of 78 males (53.42%) and 68 females (46.58%). In Group A, the mean chronological age for 5–10 years was 7.43 ± 2.32 years, and dental age was 6.85 ± 1.21 years. For 11–15 years, the mean chronological age was 13.55 ± 1.91 years, and the dental age was 12.88 ± 2.06 years. In Group B, for ages 5–10 years, the mean chronological age was 7.76 ± 2.30 years, and skeletal age was 7.08 ± 1.18 years. For 11–15 years, the mean chronological age was 12.67 ± 1.83 years, and skeletal age was 12.02 ± 0.66 years. No significant differences were found between the two methods in both age groups (p > 0.05). Conclusion: Both the dental and skeletal methods for forensic age estimation are accurate and effective. No significant differences were observed between the two methods, making either suitable for forensic age assessment. Keywords: Forensic Age Estimation, Dental Age (Demirjian Method), Skeletal Age (Greulich and Pyle Method), Carpal Bone Ossification, Pediatric Age Assessment